Mixing characteristics and energy conversion in the coalescence process of the two droplets. (2nd February 2022) - Luo, Xiaoming; Xu, Ke; Li, Wanrui; Huang, Xin; He, Limin
Graphical abstract: Highlights: Five droplet mixing modes are found. The mixing modes are transformed by altering droplet size and interfacial tension. A phase diagram of droplet mixing modes is obtained. A novel model is built to reveal energy distribution mechanism of droplet mixing. An evaluation criterion for mixing efficiency of the droplets is proposed. Abstract: In the case of fluid flow with a low Reynolds number, the internal fluid stratification can be easily observed after droplet coalescence, impeding rapid mixing of fluid. In this study, the capillary pressure difference is increased by adjusting the droplet size and the interfacial tension, so that a strong jet can be generated, resulting in a rapid mixing. Five distinct droplet mixing modes have been found. The phase diagram of the droplet mixing modes is obtained and the transition rule of the droplet mixing modes is established on this basis. A novel energy distribution model is employed to analyze the dependence between liquid bridge expansion and jet movement of two droplets. In addition, a criterion for evaluating the mixing efficiency of droplets is presented. The results presented in this paper provide a theoretical basis and practical guidance for realizing the efficient mixing of microfluids.